Towards 21-cm intensity mapping at z = 2.28 with uGMRT using the tapered gridded estimator – IV. Wide-band analysis - Elahi K.M.A.; Bharadwaj S.; Pal S.; Ghosh A.; Ali Sk.S.; Choudhuri S.; Chakraborty A.; Datta A.; Roy N.; Choudhury M.; Dutta P. (My University, 2025)
We present a Wide-band tapered gridded estimator (TGE), which incorporates baseline migration and variation of the primary beam pattern for neutral hydrogen (H i) 21-cm intensity mapping (IM) with large frequency bandwidth radio-interferometric observations. Here we have analysed 394 − 494 MHz (z = 1.9–2.6) uGMRT data to estimate the Multifrequency Angular Power Spectrum (MAPS) Cℓ(∆ν) from which we have removed the foregrounds using the polynomial fitting (PF) and Gaussian Process Regression (GPR) methods developed in our earlier work. Using the residual Cℓ(∆ν) to estimate the mean-squared 21-cm brightness temperature fluctuation ∆2(k), we find that this is consistent with 0 ± 2σ in several k bins. The resulting 2σ upper limit ∆2(k) < (4.68)2 mK2 at k = 0.219 Mpc−1 is nearly 15 times tighter than earlier limits obtained from a smaller bandwidth (24.4 MHz) of the same data. The 2σ upper limit [ΩH ibH i] < 1.01 × 10−2 is within an order of magnitude of the value expected from independent estimates of the H i mass density ΩH i and the H i bias bHi. The techniques used here can be applied to other telescopes and frequencies, including ∼ 150 MHz Epoch of Reionization observations. © 2024 The Author(s). Published by Oxford University Press on behalf of Royal Astronomical Society.